TEACHERS’ ROLES IN DEVELOPING THE MERDEKA CURRICULUM FROM AN ISLAMIC EDUCATION PERSPECTIVE: A CASE STUDY OF A VOCATIONAL SCHOOL - Salsabila Putry Zaen; Sintia Dwi Rahmadini; Muhammad Zaidaan Arkaan (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study examines the implementation and evaluation of the Merdeka Curriculum at SMK Negeri 12 Malang from the perspective of Islamic Education Management. Using a qualitative case study approach, data were collected through observations, in-depth interviews with school leaders and teachers, and document analysis. The findings indicate that teachers play a central role not only as curriculum implementers but also as collaborators, evaluators, and reflective practitioners. Curriculum enactment is characterized by cross-subject collaboration, project-based learning, teaching factory programs, and continuous formative evaluation aligned with industry needs. From an Islamic educational perspective, these practices embody core values such as amanah (accountability), syūra (consultative decision-making), itqān (professional excellence), and muhāsabah (reflective self-evaluation), which strengthen both instructional quality and moral development. However, the study also identifies challenges, including administrative workload, uneven teacher readiness, limited infrastructure, misalignment between vocational learning and academically oriented national assessments, and inconsistent industry participation. The study concludes that successful implementation of the Merdeka Curriculum in vocational schools depends on sustained teacher collaboration, supportive instructional leadership, strong industry partnerships, and value-based reflective practices. This research contributes an empirically grounded and Islamically informed perspective to the discourse on vocational curriculum reform in Indonesia.